2023
DOI: 10.1038/s41467-023-38268-0
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic electron ptychographic single particle analysis with wide bandwidth information transfer

Abstract: Advances in cryogenic transmission electron microscopy have revolutionised the determination of many macromolecular structures at atomic or near-atomic resolution. This method is based on conventional defocused phase contrast imaging. However, it has limitations of weaker contrast for small biological molecules embedded in vitreous ice, in comparison with cryo-ptychography, which shows increased contrast. Here we report a single-particle analysis based on the use of ptychographic reconstruction data, demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Moreover, our reference images are formed by amplitude contrast which is less efficient than phase contrast for SPA samples, which are generally thin and composed of light elements. STEM SPA resolution can potentially be improved by phase retrieval methods [23,24]. Practical considerations constrain the combination of these methods with EELS but hold promise for the future [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our reference images are formed by amplitude contrast which is less efficient than phase contrast for SPA samples, which are generally thin and composed of light elements. STEM SPA resolution can potentially be improved by phase retrieval methods [23,24]. Practical considerations constrain the combination of these methods with EELS but hold promise for the future [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Data processing workflows have to be established that can deal with the very low signal-to-noise ratio in the low-dose datasets and with the enormous quantity of recorded data, reaching terabytes in size for one sample. Nevertheless, significant progress in life sciences 4D-STEM has recently been demonstrated by the application of 4D-STEM ptychography to frozen-hydrated viruses 16,31 and virus-like particles 32 .…”
Section: Mainmentioning
confidence: 99%
“…iDPC-STEM has generated the first SPA map of macromolecules embedded in vitrified ice by a STEM technique at near-atomic resolution 23 . Initial attempts at low-dose ptychography have been performed on single particle VLPs at nanometer resolution with a limited number of particles 24,25 . More recent demonstrations have shown that SPA of thin sections with ptychography can resolve protein structures at a sub-nanometer level 26 , including a 5.8Å SPA map of apoferritin reconstructed from ∼11,000 particles.…”
Section: Mainmentioning
confidence: 99%